The Role Of Fintech And Sustainable Practices On Financial Reporting Quality In Jordanian Customs Clearance Companies - Ashraf Ibrahim Abdallah Qahman; Aziz Madi; Omar M.Shubailat; Murad Ali Ahmad Al-Zaqeba; Ahmed Nader AlOqaily (Innovative Research Publishing, 2025)
Indexed Publication (Tier 2)